A STRATEGY TO PROMOTE THE COMPETITIVENESS OF MICRO, SMALL AND MEDIUM ENTERPRISES (MSME) DURING THE CONDITION OF COVID 19 PANDEMICS - Rahmadani Rahmadani; Jefriyanto Jefriyanto (UNIB Press, 2021)
The research is aimed to review competitiveness strategies of Micro, Small, and Medium Enterprises (MSME) during the pandemic of Covid 19 to the MSME creative industries of Kp. Pelintahan notably. This research used primary and secondary data and used a descriptive qualitative approach for criticism to analyze the latest problems of MSME creative industries in this pandemic of Covid 19, which used semi-structured interviews, participative observation, and questionnaires for data accumulation technic. Then used AHP (Analytical Hierarchy Process) method and continued with SWOT analysis to formulate a strategy for solving it. The respondence of this research is about ten employees of MSME creative industries Kp. Pelintahan. The result of SWOT analysis is about 0,49 for IFAS and -1,54 for EFAS. Based on SWOT Matrix, the MSME Creative Industries position in Kp. Pelintahan is on 2nd Quadran for rating, which MSME Creative Industries employees of Kp. Pelintahan can take advantage of even a little strength to minimize a terrifying threat. The primary strategy is the Diversification Strategy with their salespeople to market their products MSME Creative Industries Kp. Pelintahan, which the market is reached out of Sumatera except for Lampung.